The Effectiveness of Digital Interactive Media (Live Worksheets) in Improving SPOK Sentence Structure Understanding among Deaf Students - Nadia Syifa Azzahra; Budi Susetyo; Iding Tarsidi (Jurnal Pendidikan Terapan, 2026)
This study aims to examine the effectiveness of Live Worksheets as digital interactive media in improving SPOK (Subject, Predicate, Object, Adverb) sentence structure understanding among deaf students in special education. This study employed a quantitative approach using a pre-experimental one-group pretest–posttest design involving 13 deaf students at the SMALB level of SLB Negeri Pangeran Cakrabuana selected through random sampling. Data were collected using multiple-choice and essay tests and analyzed using the Wilcoxon Signed Rank Test and N-Gain analysis. The findings showed a significant improvement in students’ understanding of SPOK sentence structure after the implementation of Live Worksheets, with the average score increasing from 52.04 in the pretest to 80.84 in the posttest and an N-Gain score of 61% categorized as moderate improvement. The Wilcoxon test result showed a significance value of 0.001 (p < 0.05), indicating a statistically significant difference between pretest and posttest scores. These findings imply that Live Worksheets can serve as an effective interactive learning medium to support Indonesian language learning, particularly sentence structure instruction for deaf students in special education settings. The originality of this study lies in the application of Live Worksheets specifically to improve SPOK sentence structure understanding among deaf students, an area that has received limited attention in previous studies.